EVALUATION DES PARAMÈTRES DE CROISSANCE DES ESSENCES FORESTIÈRES LOCALES EN PLANTATION AU TOGO : CAS DE TERMINALIA SUPERBA ENGL. & DIELS ET TERMINALIA IVORENSIS A. CHEV - Tagbi, Kossi Afedo; Radji, Raoufou; Adjonou, Kossi; Kokutse, Adzo Dzifa; Kokou, Kouami (European Scientific Journal, ESJ, 2015)
Description: In the Missahoe’s classified forest in the southwest of Togo, the area of Terminalia superba and Terminalia ivorensis plantations installed between 2000 and 2002, stands at 596.37 ha. More than a decade after their introduction, these plantations have had no growth assessment or receive any silvicultural treatment. Outcomes: The present study aims to characterize the structure of local populations of the two species to identify and plan silvicultural treatments necessary for the evolution of their stands. Methods: The evaluation of the growth parameters of both species was carried out in 80 plots of 20 m side, installed in managed strata of the forest reserve. The effect of density on the increments of the trees was appreciated. Dendrometric statements concerning the diameter at breast height (DBH) were performed. Results: For the two parameters studied, T. superba records a top height of 16.92 ± 3.04 m and an average diameter of 27.22 ± 9.51 cm after 12 years of growth, T. ivorensis reached a dominant amount of 17.40 ± 2.66 m, and an average diameter of 33.40 ± 4.10 cm for the same period. The annual diametric growth of both species was evaluated at 3.52 ± 0.2 cm / year. Conclusion:The different curves of heights obtained on different plots characterize even-aged stands in the seedling stage and fast growing to submit to regular treatment regime.